Advanced Fire & Gas Safety Control Berbasis IoT - Arta, I Kadek Cahyadi; Anggara, I Komang Agus Hari; Febriyanto, Andrian; Budiada, I Made; Sukarma, I Nyoman; Sapteka, Anak Agung Ngurah Gde (Majalah Ilmiah Teknologi Elektro, 2022)
Fire & gas safety control is a control system to secure a room / building from the danger of gas leakage or fire. In the current era, the development of building architecture requires us to always innovate in maintaining the safety of the occupants or the building itself. This research makes an Advance Fire & Gas Safety Control tool which aims to minimize false alarms, especially regarding steam. Smoke and steam can be distinguished by the level of humidity. Smoke, which is particulate matter, has a very low humidity level, while steam has a very high humidity level. This research implements NodeMCU ESP8266, MQ-2 Sensor, DHT11 Sensor, Fire Sensor, Buzzer, Firebase and Kodular, to detect fires, steam and gas leaks.